Association of the RASS Score with Intensity of Symptoms, Discomfort, and Communication Capacity in Terminally Ill Cancer Patients Receiving Palliative Sedation: Is RASS an Appropriate Outcome Measure? - Kengo Imai; Tatsuya Morita; Naosuke Yokomichi; Masanori Mori; Akemi Shirado Naito; Toshihiro Yamauchi; Hiroaki Tsukuura; Yu Uneno; Satoru Tsuneto; Satoshi Inoue (Palliative Medicine Reports, 2022)
Background: Palliative sedation is sometimes needed for refractory symptoms, and the Richmond Agitation?Sedation Scale (RASS) is one of the key measures. The primary aim of this study was to explore the association between RASS and degree of distress quantified by other measures: Item ?symptom control? of Support Team Assessment Schedule (STAS, item 2), Discomfort Scale for Dementia of Alzheimer Type (Discomfort Scale), and Noncommunicative Patient's Pain Assessment Instrument (NOPPAIN), as well as a communication capacity measured by the Communication Capacity Scale (CCS), item 4. Methods: This was a prospective observational study on terminally ill cancer patients with palliative sedation in a palliative care unit of a designated cancer hospital. Primarily responsible palliative care physicians rated RASS, Discomfort Scale, NOPPAIN, and CCS just before sedation and 1, 4, 24, and 48 hours after, and ward nurses rated STAS at the same time. Since the ward nurses evaluated STAS during palliative sedation, we regarded STAS as a standard of distress measure. Results: A total of 249 assessments were performed for 55 patients. RASS was moderately to highly associated with symptom intensity measured by STAS, discomfort measured by the Discomfort Scale, and pain measured by NOPPAIN (r?=?0.63 to 0.73). But communication capacity measured by CCS is not parallel with RASS and demonstrated a valley shape. In 82 assessments with an RASS score of ?1 to ?3, 11 patients (13%) had physical symptoms of STAS of 2 or more. Conclusions: RASS can roughly estimate physical distress in patients with palliative sedation, but a measure to more precisely quantify the symptom experience is needed.